Prevalence of parasitic infections in HIV-positive patients in southern Ethiopia: A cross-sectional study - Fekadu, Sintayehu; Taye, Kefyalew; Teshome, Wondu; Asnake, Solomon (The Journal of Infection in Developing Countries, 2013)
Introduction: Intestinal parasitic infectionsare a major public health burden in tropical countries. Although all HIV/AIDS patients are susceptible to parasitic infections, those having lower immune status are at greater risk. The aim of this study was to determine the prevalence of intestinal parasitic infections in patients living with HIV/AIDS. Methodology: This was a facility-based cross-sectional study. A total of 343 consecutively sampled HIV/AIDS patients from the HIV care clinic of Hawassa University Referral Hospital were included. Subjects were interviewed for demographic variables and diarrheal symptoms using structured questionnaires. Stool examinations and CD4 cells counts were also performed. Results: The prevalence of intestinal parasitic infection was 47.8% among HIV/AIDS patients; single helminthic infection prevalence (22.7%) was higher than that the prevalence of protozoal infections (14.6%). About 54% of study participants had chronic diarrhea while 3.4% had acute diarrhea. The prevalence of intestinal parasites in patients with chronic diarrhea was significantly higher than in acute diarrhea (p <0.05). Non-opportunistic intestinal parasite infections such as Ascaris lumbricoides, Taenia spp., and hookworm were commonlyfound, regardless of immunestatus or diarrheal symptoms. Opportunistic and non-opportunistic intestinal parasitic infection were more frequent in patients with a CD4 count of <200/mm3 (OR=9.5; 95% CI: 4.64-19.47) when compared with patients with CD4 counts of >=500 cells/mm3. Conclusions: Intestinal parasitic infections should be suspected in HIV/AIDS-infected patients with advanced disease presenting with chronic diarrhea. Patients with low CD4 counts should be examined critically for intestinal parasites, regardless of diarrheal status.